2020
DOI: 10.26452/ijrps.v11ispl1.2736
|View full text |Cite
|
Sign up to set email alerts
|

Covid-19 and education system: impact of current pandemic on adaptive learning strategies in medical education system

Abstract: In the last few months, the globe has been overwhelmed by the pandemic coronavirus as the number of increasing documented cases, and death rates have continued to be reported. The disease is mild in most people usually aged people and those with the coexistence of multiple disorders alongside a primary disorder, pneumonia, acute respiratory distress syndrome (ARDS), and multiorgan dysfunction may develop. No special or specific drugs/medications are available. Neither vaccine has been developed, nor is any pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 7 publications
0
6
0
1
Order By: Relevance
“…The reviewed studies indicated that technological barriers (e.g., software and hardware), weak servers without the capacity for high user volume, and systems with poor visual communication with the audience adversely affect online learning. Unreliable internet service, internet connection, internet costs and financial support issues, frequent power outages (power fluctuation), and network issues (poor bandwidth) were among the other challenges identified in the previous studies in this regard (10,12,13,(15)(16)(17)(18)(19)(20).…”
Section: Structural Challengesmentioning
confidence: 97%
See 2 more Smart Citations
“…The reviewed studies indicated that technological barriers (e.g., software and hardware), weak servers without the capacity for high user volume, and systems with poor visual communication with the audience adversely affect online learning. Unreliable internet service, internet connection, internet costs and financial support issues, frequent power outages (power fluctuation), and network issues (poor bandwidth) were among the other challenges identified in the previous studies in this regard (10,12,13,(15)(16)(17)(18)(19)(20).…”
Section: Structural Challengesmentioning
confidence: 97%
“…According to most studies, lack of infrastructures and technologies is another barrier to medical education, which is more prominent in lowand middle-income developing countries (15). Moreover, lack of access to the internet, lack of proper structures, presence of socially vulnerable students, and sociocultural norms were identified as the barriers to online learning (10,13,16,17).…”
Section: Structural Challengesmentioning
confidence: 99%
See 1 more Smart Citation
“…[19][20][21][22][23]. Few more related studies on impact of Covid-19 were reported [24][25][26][27].…”
Section: Resuming Life After Covid 19 Lockdownmentioning
confidence: 99%
“…Como consecuencia del crecimiento de los contagios por la COVID-19, los países del mundo comenzaron a establecer políticas estratégicas con extrema prioridad de aplicación, a fin de reducir el rápido avance de la enfermedad, estas medidas para contrarrestar a la COVID-19 son diferentes dependiendo de cada sector de aplicación, en la salud se presentó la limitación de atención en clínicas y hospitales, en lo social el distanciamiento social obligatorio fue la norma establecida y en educación la implementación de métodos de formación a distancia que suponen grandes retos tanto para las instituciones como para los estudiantes (Patil y Naqvi, 2020).…”
Section: Introductionunclassified